ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 1 GEDANGAN SIDOARJO - NURUL HIDAYATI (Jurnal Pendidikan Akuntansi (JPAK), 2013)
This study purpose to determine the learning media for teacher in SMA Negeri 1 Gedangan Sidoarjo and the reasons teachers choose the learning media, determine the feasibility of learning media, and study the response of students to the learning media used. This study is a descriptive research with quantitative approach. The results showed that the learning media used in SMA Negeri 1 Gedangan Sidoarjo is "Powerpoint" media and “whiteboard”. From the review of learning media expert obtained the result that the learning media “Powerpoint” used in SMA Negeri 1 Gedangan Sidoarjo has categorized decent. The results of the students responses to the learning media they use are good.. Keyword: learning media